2006
DOI: 10.1002/bio.898
|View full text |Cite
|
Sign up to set email alerts
|

A thermoluminescence study of the effects of nitrite on photosystem II in spinach thylakoids

Abstract: The site of action of nitrite on PS II was investigated by measuring the TL profile of nitrite-treated spinach thylakoid membranes. Three bands were observed in control, which were identified as the Q band (7 degrees C), the B band (24 degrees C) and the C band (57 degrees C). In the presence of 20 mmol/L nitrite, the intensity of the Q band decreased, the B band upshifted to 46 degrees C but the C band disappeared. The suppression of the Q band and the upshift of the B band suggested that nitrite caused inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(29 reference statements)
3
5
0
Order By: Relevance
“…6). Our TL data are consistent with the observation of Sahay et al (31) that nitrite inhibited the OEC on the donor side of PSII, as indicated by the suppression of the Q band and the upshift of the B band in nitrite-treated isolated chloroplasts. The increase in the stability of the S 2 state arises from the inactivation of the donor side (43).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…6). Our TL data are consistent with the observation of Sahay et al (31) that nitrite inhibited the OEC on the donor side of PSII, as indicated by the suppression of the Q band and the upshift of the B band in nitrite-treated isolated chloroplasts. The increase in the stability of the S 2 state arises from the inactivation of the donor side (43).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the reaction center is a more sensitive target of nitrite stress than is the donor side of PSII. Our results therefore broaden the incomplete view that the donor side of PSII is the primary target of nitrite stress (31). measured at 100 ms after the fourth flash (ΔF 4 ϭ F 400 ms /F o Ϫ 1), which is controlled almost entirely by inactive centers.…”
Section: Discussionsupporting
confidence: 62%
“…These results, thus, suggested that the effects of nitrite were mainly on the donor side of PS II. Our results are in good agreement with the earlier reports (Sahay et al 2006a, 2006b), which suggested that the effects of nitrite are on the donor side of PS II.…”
Section: Discussionsupporting
confidence: 94%
“…Further, Jajoo and Bharti (1993) showed that the presence of chloride lowers the amount of bicarbonate required to overcome the inhibition induced by nitrite or formate. Loss of S 2 state multiline signal (Jajoo et al 2005) and changes observed in the thermoluminescence studies (Sahay et al 2006b) in nitrite‐treated samples have shown that nitrite probably acts on the donor side of PS II.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous stepwise shift in the peak position of the B-band indicated, however, that S 3 Q B − charge recombination is more resistant to Cu (II). Nitrite, but not formate, fluoride or nitrate anions, inhibited PSII in spinach thylakoids, probably at the donor side (Sahay et al, 2006).…”
mentioning
confidence: 88%